Early Cholecystectomy versus Conservative Management in Mucocele Gall Bladder - Dileep Kumar, Muhammad Afzal, Muhammad Umair Samee, Shahid Hussain Mirani, Tayyaba Rasheed (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To compare the early cholecystectomy versus conservative management in mucocele gall bladder. Study design: Retrospective study Place and duration of study: Department of General Surgery, Ward-2, JPMC/Jinnah Sindh Medical University, Karachi from 1st October 2020 to 30th September 2022. Methodology: One hundred patients suffering from cholelithiasis with mucocele gall bladder were included. The patients were divided into two groups on the basis of stone location. Group 1 was those where the stone was found on the base of common bile duct (CBD) and elective/early surgery was conducted for the cases of cholelithiasis. Group 2 was those where conservative/delayed surgical technique was applied due to stone location not in the CBD for treatment. While in each group there were 50 cases which were age and gender matched. The first priority for surgical option was through laparoscopic surgery. Results: The mean age of the patients was 45.2±3.3 years. Out of the total cases in group 1 the process of ERCP was conducted in 64% of the cases before laparoscopy. There were 1% and 10% cases which were shifted to open surgery from laparoscopic in group1 and 2 respectively. Consequently, the mean operative time and hospital duration was increased in group 2. Within the Group 2 cases the risk of sepsis, wound contamination and perforation of gall bladder was much higher than in the Group 1 by a value of 10%, 12% and 6% respectively. There was 1 case of mortality and 2 cases of pancreatitis in group 2. Conclusion: The early cholecystectomy is a much safer and efficient procedure on treatment of mucocele gall bladder cases verses conservative management. Keywords: Early cholecystectomy, Conservative management, Mucocele gall bladder